The New England mind, from colony to province - Miller, Perry, 1905-1963 (Belknap Press of Harvard University Press, 1983)
The New England Mind: From Colony to Province is one of Perry Miller's masterworks, exploring the intellectual history of the Puritans through a deep investigation of the thought of the Puritan divines. In this book, as well as its predecessor The New England Mind: The Seventeenth Century, Miller asserts a single intellectual history for America that could be traced to the Puritan belief system.
"Sequel to The New England mind: the seventeenth century"--Foreword
Reprint. Originally published: Cambridge [Mass.] : Harvard University Press, 1953.
"This book has been digitally reprinted. The content remains identical to that of previous printings." -- Title page verso
Keywords: New England -- Intellectual life.; New England -- History -- Colonial period, ca. 1600-1775.; American literature -- Puritan authors -- History and criticism.; American literature -- New England -- History and criticism.; Puritans -- New England.; New England theology.; Nouvelle-Angleterre -- Vie intellectuelle.; Nouvelle-Angleterre -- Histoire -- ca 1600-1775 (Période coloniale); Littérature américaine -- Auteurs puritains -- Histoire et critique.; Puritains -- Nouvelle-Angleterre.; Théologie de la Nouvelle-Angleterre.; HISTORY -- State & Local.; HISTORY -- State & Local -- General.; HISTORY -- United States -- General.; American literature; American literature -- Puritan authors; Intellectual life; New England theology; Puritans; New England; 1600-1775; Criticism, interpretation, etc.; History